Microglia metabolism in health and disease - Borst, Katharina; Schwabenland, Marius; Prinz, Marco (Neurochemistry international, 2019)
In the last decade tremendous progress has been made in understanding how the immune system reacts to insults. During this progress it became obvious that those immune responses are tightly regulated and cross-linked with distinct metabolic changes in immune cells. Extensive research has been conducted mainly on subtypes of T cells, which use different metabolic pathways during differentiation processes and activation states. In addition, it has also been established later, that the innate immune cell lineage of myeloid cells includes a variety of different subsets of bone marrow-derived as well as tissue-specific macrophages, which elicit much more functions than simply killing bacteria. To execute this high variety of functions, also macrophages use different metabolic pathways and are tightly regulated by key metabolic regulators, such as the mechanistic target of rapamycin (mTOR). Upon activation, metabolic changes within the cell occur to meet the requirements of the phenotypic switch. In addition, metabolic changes correlate with the ability of innate immune cells to show hallmarks of adaptive immune responses. Little is known about specific metabolic changes of myeloid cells and specifically microglia in vivo. Microglia are key players in neurodegenerative and neuroinflammatory diseases and have become a major target of medical research. Here, we review the existing data on microglia metabolism and the connection of microglia phenotypes with neuroinflammatory and neurodegenerative diseases. Lastly, we will discuss how our knowledge about the cellular metabolism might be used to develop new treatment options for neurological diseases. •Microglia are key players in neurodegenerative and neuroinflammatory diseases.•Metabolic changes in immune cells lead to distinct immune responses.•Manipulation of microglia metabolism can be considered as a treatment option.